2017
DOI: 10.1111/iwj.12715
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intramuscular human placenta‐derived mesenchymal stromal‐like cells (cenplacel [PDA‐002]) in patients who have a diabetic foot ulcer with peripheral arterial disease

Abstract: The objective of this study was to examine the safety of cenplacel (PDA‐002) in patients with peripheral arterial disease (PAD) and a diabetic foot ulcer (DFU). Cenplacel is a mesenchymal‐like cell population derived from full‐term human placenta. This phase 1, dose‐escalation study investigated cenplacel in diabetic patients with chronic DFUs (Wagner grade 1 or grade 2) and PAD [ankle‐brachial index (ABI) >0·5 and ≤0·9], enrolled sequentially into each of four dose cohorts (3 × 106, 10 × 106, 30 × 106 and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
(27 reference statements)
0
21
0
3
Order By: Relevance
“…Some considerations to keep in mind are: avoidance of irritating compounds or accidental nerve injection, which may lead to paresis, paralysis, localized muscle fiber destruction, and even necrosis [83,84]. New therapies are recently being explored using this route, such as the intramuscular administration of human placenta-derived mesenchymal stromal-like cells for patients who have a diabetic foot ulcer with peripheral arterial disease [85].…”
Section: Administration Routesmentioning
confidence: 99%
“…Some considerations to keep in mind are: avoidance of irritating compounds or accidental nerve injection, which may lead to paresis, paralysis, localized muscle fiber destruction, and even necrosis [83,84]. New therapies are recently being explored using this route, such as the intramuscular administration of human placenta-derived mesenchymal stromal-like cells for patients who have a diabetic foot ulcer with peripheral arterial disease [85].…”
Section: Administration Routesmentioning
confidence: 99%
“…Quin et al 169 derived from the full-term human placenta) has been reported so far using FAD-MSCs. 171 A summary of clinical trials that investigates the healing potential of FAD-MSCs, registered on the website of the clinical trials data bank at the National Institutes of Health (www.clinicaltrials.gov) is listed in Table 4.…”
Section: Clinical Trials Using Fetal Adnexa Derived Mscs In Wound Healingmentioning
confidence: 99%
“…Among the different cells applied by injectable cell solutions are included MSCs (NCT02669199, NCT01750749), human autologous adipose‐derived stromal vascular fraction (NCT01813279), bone marrow‐derived cells (NCT01750749), human placenta‐derived cells (NCT01859117), melanocytes and keratinocytes (NCT02510651), and even human umbilical cord blood derived‐universal stem cells (NCT01927705). With the use of intramuscular human placenta‐derived mesenchymal stromal‐like cells in patients with peripheral arterial disease (PAD) and a diabetic foot ulcer (DFU), preliminary evidence of ulcer healing was shown in seven out of 15 patients, and circulating endothelial cell levels (as a vascular trauma in peripheral artery disease biomarker) were decreased within 1 month (NCT01859117) …”
Section: Current and Future Clinical Applicationsmentioning
confidence: 99%
“…With the use of intramuscular human placenta-derived mesenchymal stromal-like cells in patients with peripheral arterial disease (PAD) and a diabetic foot ulcer (DFU), preliminary evidence of ulcer healing was shown in seven out of 15 patients, and circulating endothelial cell levels (as a vascular trauma in peripheral artery disease biomarker) were decreased within 1 month (NCT01859117). 82 Regarding human umbilical cord blood derived-universal stem cells (hUCB-MSCs), clinical application in the treatment of atopic dermatitis (AD) demonstrated for the first time, marked an improvement of AD features with cell therapeutics without noteworthy adverse events. 83 Nevertheless, other cell-based products such as the use PRP (NCT02832583), platelet- Therapeutic strategies for skin healing rich-fibrin (NCT01957124) and amnion-derived cellular cytokine (NCT02389777, NCT01715012) are being addressed.…”
Section: Current and Future Clinical Applicationsmentioning
confidence: 99%